Peningkatan Kemampuan Berhitung Melalui Permainan Jemuran Pintar di Taman Kanak-kanak Aisyiyah 5 Andalas Padang - Rini Meinarti; Prima Aulia (RC-INSTITUT, 2020)
The research aims to increase the ability to count in early childhood at kindergarten Aisyiyah 5 Andalas Padang. The type of research is the action class research, which is the observation of an intentional activity in class. The qualitative and quantitative data analysis technique performed on students uses the percentage approach. On the first cycle of the three meetings, the counting development of children reaches fifty-two percents and it does not fulfill the criteria of the minimum exhaustiveness yet. On the second one, there is an increase in counting and it developed very well to be eighty-eight percent so that the result fulfills the criteria of the minimum exhaustiveness. The result shows that the smart clothesline game is able to increase the ability to count in early childhood at kindergarten Aisyiyah 5 Andalas Padang.